Optimalisasi Pelayanan Klinis Melalui Clinical Pathway: Analisis Pengetahuan dan Sikap Praktisi Medis - Sugiarti, Ida; Wahyuni, Ida; Sukawan, Ari (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2025)
Dr. Soekardjo Hospital has a clinical pathway that is currently used mainly as a requirement for accreditation rather than as a service guideline. Previous studies have found that several clinical pathway procedures were overlooked, posing a risk of potential fraud. Under the Case Base Group-based National Health Insurance system, which demands cost efficiency and quality control, clinical pathways must be understood and implemented by healthcare professionals to optimise patient care. This study aimed to analyse the knowledge and attitudes of medical practitioners toward clinical pathway strategies. A quantitative research design was applied, with data collected through questionnaires completed by 30 respondents. Univariate analysis was used to describe respondent characteristics, while bivariate analysis with the chi-square test assessed variable relationships. The findings showed no significant association between education level, profession, or years of service with practitioners' knowledge and attitudes. However, a significant relationship was found between knowledge and attitude, indicating that better knowledge leads to a more positive attitude toward clinical pathway adoption. Therefore, improving knowledge is crucial. Training programmes should be developed to enhance the understanding and attitudes of medical practitioners to support the effective and consistent implementation of clinical pathways in hospital settings.